Avaliação da influência de diferentes unidades da paisagem na alocação de práticas conservacionistas em bacias hidrográficas: uma abordagem com SWAT+ - Campos, Fábio Luiz Mação (2025)
Faced growing conflicts over water resources, alternatives for better planning of land use in river basins that aim to increase water availability in times of scarcity and reduce the amount of sediment and pollutants become necessary. One of the options for increasing water availability is the application of Best Management Practices (BMPs) that increase base f low and reduce the contribution of sediment and nutrients to watercourses. However, their application can have considerable financial costs and require intervention in agricultural areas. For this reason, it is important that, in order to better use the resources available for soil and water conservation actions, the most appropriate locational alternatives are found. To identify these areas, the use of hydrological models is a highly useful tool, as they are capable of simulating in advance what the effect of applying a certain practice will be in a certain location in the basin. Although research shows that relief exerts a strong influence on water and sediment flows, there are still many questions to be understood regarding the influence of the application of BMPs in different compartments. In this context, this research contributes to the allocation of BMPs in river basins, investigating above all the influences of relief characteristics on these procedures. One of the most widely used models for assessing the impacts of this allocation, SWAT, has recently had a fully revised version resulting in the SWAT+ hydrological model. This study used the SWAT+ model to perform hydrological modeling of two small river basins and test the effect of 5 BMPs on the water balance, water balance, water and sediment yield, water availability and sediment load. The alternative scenarios showed that BMPs can be an important alternative for increasing availability and ensuring water security in river basins. In the simulated scenarios, BMPs increased minimum flow by up to 8.84% and reduced maximum flows by up to 11.01%, in addition to having a considerable impact on reference f lows for water resource allocation. It was also demonstrated how land use and relief can influence the effectiveness of BMPs and assist in the planning processes for the allocation of these practices. An experiment was also conducted to evaluate the influence of relief characteristics in different compartments of the basin through the use of the terrain roughness index. The experiment showed that the index can be an alternative parameter for planning the allocation of BMPs. The findings of the study expand knowledge about the allocation of BMPs in river basins and open up new research opportunities on the use of relief for planning interventions aimed at increasing basin resilience to climate change.